Fistula Rate after primary palatal repair with intravelarveloplasty: a retrospective three-year audit of six units (NorCleft) in the UK. Issue 6 (July 2016) - Moar, Kanwalraj K.; Sweet, Christopher; Beale, Victoria
Abstract: Our aim was to evaluate the rate of fistulation after one-stage palatal repair by intravelarveloplasty in the NorCleft Cleft Services (Scotland and Northern England), this being a primary outcome measure after repair of a cleft palate. We designed a retrospective, three-year clinical audit of six cleft units in the UK, and retrospectively reviewed the casenotes of babies with cleft palate born in 2006-2008 who were treated by intravelarveloplasty. We recorded type of cleft and procedure, including lateral relieving incisions, and our main outcome measure was the presence of a fistula behind the incisive foramen at 3 years of age, or a history of repair of a fistula. A total of 743 patients had cleft palates, but 69 (9%) were excluded (because they had not been operated on, or had not been reviewed by the age of 3 years, or their records were unavailable). A total of 626 patients had had a Sommerlad intravelarveloplasty repair, and 48 had had mixed procedures including Veau-Wardill-Kilner, Furlow, or two-stage repairs, and were not studied further. Eighty-seven (14%) who had had intravelarvoloplasty had a fistula behind the incisive foramen. There was no significant difference in age at time of repair between those who developed a fistula and those who did not (p=0.65 ). The fistula rate of 14% is comparable with that of Sommerlad. The fistula rate was higher in patients who had had lateral releasing incisions (58/275, 21%) or who had bilateral cleft palate (16/63, 25%). To our knowledge this is the largest review of the fistula rate in patients who had primary palatal repair using the intravelarveloplasty technique in the UK, and shows significant correlation between lateral releasing incisions and formation of a fistula, except in the unilateral cleft lip and palate group (p=0.12 ).